Sustained Maximal Voluntary Contractions Elicit Different Neurophysiological Responses in Upper- and Lower-Limb Muscles in Men. (1st December 2019) - Temesi, John; Vernillo, Gianluca; Martin, Matthieu; Krüger, Renata L.; McNeil, Chris J.; Millet, Guillaume Y.
Highlights: Reduced motoneuron excitability in biceps brachii but not rectus femoris, with similar rise in corticospinal excitability. Greater inhibition in rectus femoris after spinal vs cortical stimulation but similar inhibition after both in biceps brachii . Changes in excitability of motor cortex and motoneurons during the same fatiguing exercise are limb/muscle specific. Abstract: This study compared the effects of fatigue on corticospinal responsiveness in the upper- and lower-limb muscles of the same participants. Seven healthy males performed a 2-min maximal voluntary isometric contraction of the elbow flexors or knee extensors on four separate days. Electromyographic responses were elicited by nerve stimulation (maximal M-wave) in all sessions and by transcranial magnetic stimulation (motor-evoked potential; silent period) and spinal tract stimulation (cervicomedullary or thoracic motor-evoked potentials; silent period) in one session each per limb. During sustained maximal voluntary contractions, motor-evoked potential area normalised to M-waves increased from baseline in biceps brachii (155 ± 55%) and rectus femoris (151 ± 44%) (both p ≤ 0.045). At the end of maximal voluntary contractions, spinal tract motor-evoked potential area normalised to M-waves was smaller than baseline in biceps brachii (74 ± 23%; p = 0.012) but not rectus femoris (108 ± 40%; p = 0.999). The ratio of motor-evoked potential to spinal tract-evoked potential areas increased dramatically from 90 to 115 s in biceps brachii (p = 0.001) but not in rectus femoris (p = 0.999). Silent period durations increased similarly in both muscles (p ≤ 0.008) after transcranial and spinal stimulation. Sustained maximal contractions elicit different neurophysiological adjustments in upper- and lower-limb muscles. Specifically, motoneuronal excitability was reduced in biceps brachii, but not in rectus femoris, and this reduction required greater compensatory adjustments from the motor cortex. Therefore, changes in cortical and spinal excitability during sustained maximal exercise are likely specific to the muscle performing the task.